PERBEDAAN PERSEPSI PETANI TERHADAP PROGRAM KARTU TANI DI KECAMATAN KALIJAMBE KABUPATEN SRAGEN - Koko Widyat Moko; Suwarto Suwarto; Bekti Wahyu Utami (Universitas Sebelas Maret, 2017)
The aims of this research is to analyze the differences in the farmers’ perception to Farmers’ Card program in Kalijambe District Sragen Regency based on the environment of farmers among the farmers who have long distance access from the District Office and Bank BRI with the farmers who have at close range access from the District Office and Bank BRI and based on the position of farmers in farmers’ group, they are management and members of farmers’ group. The basic method of this research is descriptive quantitative and survey techniques. The method of Location determination was done purposively in Kalijambe District Sragen Regency by taking two farmer groups they are farmers’ group Tani Santoso Banaran village and farmers’ group Ngudi Mulyo Wonorejo village. The population of this research was a farmer who is included/listed in the program Farmers’ Cards in Kalijambe District Sragen Regency, with the number of farmers’ responder 60 peoples. The sample is determined by using multi-stage cluster random sampling. The Analysis of data used is the different test of U Mann Whitney. The results showed that there were significant differences in the perception of the Farmers’ Card program based on the environment of farmers and farmers’ position in farmers’ group. The differences of perceptions based on their environment showed that the farmers’ perception whose close access to the District Office and Bank BRI is better than the perception of farmers whose long distance access from the District Office and Bank BRI. Based on the farmers’ position in farmers’ group, it is showed that the farmers’ perception in farmers’ management is better than the farmers’ perception in farmers’ member.